Voices of the Costa Rican scientific diaspora: Policy lessons from a decade of experiences from our scientists abroad - Jarquin-Solis, Maria Esteli; Lin-Shiao, Enrique; Guerra, Melania; Calderón Zúñiga, Karlissa; Mora Solórzano, Dayana; Gutiérrez, José María (Frontiers in Research Metrics and Analytics, 2022)
Scientific diasporas have been identified as valuable resources to strengthen science, technology, and innovation in their countries of origin. In this context, our paper seeks to contribute by addressing the following research questions: What are the main features of the Costa Rican scientific diaspora, and what policy lessons can be extracted from their experiences abroad? Toward this goal, we analyzed ten years of diaspora perspectives as collected by TicoTal, an online database and network of Costa Rican scientists studying and working abroad created by the National Academy of Sciences (ANC) in 2010. Our study reveals the main features of the Costa Rican scientific diaspora using 121 interviews published over a ten-year period: we identified the academic areas in which the diaspora has specialized, the countries where they were trained, their current location, the most frequent funding mechanisms and sources that enabled professional opportunities abroad, the level of engagement and collaboration they maintain with the Costa Rican STI ecosystem, along with the incentives they consider important to support and harness the potential of this community to advance STI goals in the country. Results from this analysis can inform national policies and investment strategies in R&D infrastructure and resources, by providing a roadmap to engage with scientific diasporas and benefit from their training and talent, as well as guide future scholarship and exchange programs.